Development and Evaluation of Hourly and Kilometer Resolution Retrospective and Real-Time Surface Meteorological Blended Forcing Dataset (SMBFD) in China - Han, Shuai; Shi, Chunxiang; Xu, Bin; Sun, Shuai; Zhang, Tao; Jiang, Lipeng; Liang, Xiao (Journal of Meteorological Research, 2019)
A real-time, long-term surface meteorological blended forcing dataset (SMBFD) has been developed based on station observations, satellite retrievals, and reanalysis products in China. The observations are collected at national and regional automatic weather stations, satellite data are obtained from the Fengyun (FY) series satellites retrievals, and the reanalysis products are obtained from the ECMWF. The 90-m resolution digital terrain elevation data in China are obtained from the Shuttle Radar Topographic Mission (SRTM) for temperature and humidity elevation adjustment. The dataset includes 2-m air temperature and humidity, 10-m zonal and meridional winds, downward shortwave radiation, surface pressure, and precipitation. The spatial resolution is 1 km, and the temporal resolution is 1 h. During the data processing procedure, various data fusion techniques including the space-time multiscale variational analysis, the discrete ordinates radiative transfer (DISORT) model, the hybrid radiation estimation model, and a terrain correction algorithm are employed. Dependent and independent evaluations of the dataset are performed against observations. The SMBFD dataset is also compared with similar datasets produced in other major meteorological operational centers in the world. The results are as follows. (1) All variables show reasonable geographic distribution features and realistic spatial and temporal variations. (2) Dependent and independent evaluations both indicate that the gridded SMBFD dataset is close to the observations, while the dependent evaluation yields better results than the independent evaluation. (3) Compared with similar datasets produced in other meteorological operational centers, the real-time and retrospective surface meteorological fusion data obviously have higher quality. The dataset introduced in the present study is in general stable and accurate, and can be applied in various practice such as meteorology, agriculture, ecology, environmental protection, etc. Meanwhile, this dataset has been used as the atmospheric forcing data to drive the operational High-resolution Land Data Assimilation System of China Meteorological Administration. The dataset with the network Common Data Form (NETCDF) can be decoded by various programming languages, and it is freely available to non-commercial users.